Campur Kode Tuturan Guru dalam Proses Belajar Mengajar: Studi Kasus di Kelas VII SMPN 20 Padang - Murliaty, Murliaty; Gani, Erizal; Tamsin, Andria Catri (Universitas Negeri Padang, 2013)
The purpose of this research is to describe the code mixing of Indonesian language teachers’ utterance while teaching learning process. The type of the research is qualitative, which use descriptive method. Furthermore, the data of the research is the Indonesian language teachers’ utterance. It contains the code mixing. The result of the research shows that the dominant code mixing is happen to the teacher while teaching learning process. The aim is to prove the teachers’ position or teachers’ intelegency. So that, code mixing that did by Indonesian language teacher in Junior High School 20 Padang, is the negative code mixing (not good).